MANFAAT PENGGUNAAN BUILDING INFORMATION MODELLING (BIM) PADA PROYEK KONSTRUKSI SEBAGAI MEDIA KOMUNIKASI STAKEHOLDERS - raflis raflis; bambang endro yuwono; Ripsky Rayshanda (Universitas Trisakti, 2018)
Construction projects are becoming much more complex and difficult to manage, reciprocal interdependence between stakeholders is one of the causes, such as architects, civil engineers and mechanical. Building Information Modelling (BIM) not only allows the geometrical modelling butalso useful for management of construction project especially in communication between stakeholders. The aims of this papers is to find out the project benefit of BIM as a media communication. Data collection is done by distributing questionnaires to large companies both contractor or engineering consultants in DKI Jakarta who have used BIM in communication process. The data is processed by using the structural equation modeling (SEM) method and It was found that the use of BIM could facilitate stakeholders involved in the construction project work team in communicating and coordinating.